2020
DOI: 10.2196/19669
|View full text |Cite
|
Sign up to set email alerts
|

Availability and Quality of Web Resources for Parents of Children With Disability: Content Analysis and Usability Study

Abstract: Background The internet is a valuable resource for parents of typical children, who are looking for information about their children’s growth and development and how to boost them. However, for parents of children with special needs, especially for non–English-speaking parents, there are anecdotal reports stating that specific and accurate information is not available on the internet. Objective This study aims to describe the type of information availab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 39 publications
1
4
0
4
Order By: Relevance
“…Therefore, website evaluations commonly use a variety of methodologies, including measures of usability (SUS and task performance), self-reports (surveys), qualitative interview-based methods, or Google Analytics to investigate website behaviors (use and interaction) [ 44 - 47 ]. Similar to a recent study, we did not find published recommendations for procedures to conduct a review of a live website in a systematic manner [ 48 ]. A recent systematic review found that despite there being many published toolkits, very few were evaluated, and the authors concluded that this is an area where greater attention and rigorous methodology are needed [ 20 ].…”
Section: Discussionsupporting
confidence: 78%
“…Therefore, website evaluations commonly use a variety of methodologies, including measures of usability (SUS and task performance), self-reports (surveys), qualitative interview-based methods, or Google Analytics to investigate website behaviors (use and interaction) [ 44 - 47 ]. Similar to a recent study, we did not find published recommendations for procedures to conduct a review of a live website in a systematic manner [ 48 ]. A recent systematic review found that despite there being many published toolkits, very few were evaluated, and the authors concluded that this is an area where greater attention and rigorous methodology are needed [ 20 ].…”
Section: Discussionsupporting
confidence: 78%
“…Therefore, website evaluations commonly use a variety of methodologies, including measures of usability (SUS and task performance), self-reports (surveys), qualitative interview-based methods, or Google Analytics to investigate website behaviors (use and interaction) [44][45][46][47]. Similar to a recent study, we did not find published recommendations for procedures to conduct a review of a live website in a systematic manner [48]. A recent systematic review found that despite there being many published toolkits, very few were evaluated, and the authors concluded that this is an area where greater attention and rigorous methodology are needed [20].…”
Section: Comparison With Previous Workmentioning
confidence: 72%
“…The responses collected from Quora [ 52 ] also suggested continuous changes in the features of the app so as to adapt it to the behavior of children with ASD during their different levels of development. This was supported by the study by Buteau-poulin et al [ 67 ], in which the authors recommended the regular update of information related to special education of children with disabilities that is available online. Participants from the Quora platform said that children can learn anything from digital devices even in cases where they tend not to look at the instructor during their class hours.…”
Section: Discussionmentioning
confidence: 84%